EVALUASI PELAKSANAAN PERATURAN DAERAH TENTANG ALOKASI DANA DESA - Faradillah Paratama (Fakultas Syariah Institut Agama Islam Negeri Palu, 2018)
Every regency government has issued Regulation on the allocation of village funds (ADD) ADD funding as a reference. Granting rights ADD is a form of fulfillment of village autonomy within the framework of the implementation of the village. The implementation on the ground quite well, begin from planning phase has been implemented well until completion of the ADD planning in village regulations. Furthermore, the implementation phase is also running smoothly and fairly good. But there are still a few obstacles which funds ADD does not coincide with the time the cause of a delay so that the activity is late to be implemented as well as the distribution system funds change often.